CHOLINESTERASES, A TARGET OF PHARMACOLOGY AND TOXICOLOGY - Pohanka, Miroslav (Biomedical papers, 2011)
Background: Cholinesterases are a group of serine hydrolases that split the neurotransmitter acetylcholine (ACh) and terminate its action. Of the two types, butyrylcholinesterase and acetylcholinesterase (AChE), AChE plays the key role in ending cholinergic neurotransmission. Cholinesterase inhibitors are substances, either natural or man-made that interfere with the break-down of ACh and prolong its action. Hence their relevance to toxicology and pharmacology.Methods and Results: The present review summarizes current knowledge of the cholinesterases and their inhibition. Particular attention is paid to the toxicology and pharmacology of cholinesterase-related inhibitors such as nerve agents (e.g. sarin, soman, tabun, VX), pesticides (e.g. paraoxon, parathion, malathion, malaoxon, carbofuran), selected plants and fungal secondary metabolites (e.g. aflatoxins), drugs for Alzheimer's disease (e.g. huperzine, metrifonate, tacrine, donepezil) and Myasthenia gravis (e.g. pyridostigmine) treatment and other compounds (propidium, ethidium, decamethonium).Conclusions: The crucial role of the cholinesterases in neural transmission makes them a primary target of a large number of cholinesterase-inhibiting drugs and toxins. In pharmacology, this has relevance to the treatment of neurodegenerative disorders.
Keywords: Acetylcholinesterase/Butyrylcholinesterase/Alzheimer's disease/Myasthenia gravis/Huperzine/Donepezil/Rivastigmine/Galantamine